2021
DOI: 10.1016/j.isci.2021.103093
|View full text |Cite
|
Sign up to set email alerts
|

Ezh2 harnesses the intranuclear actin cytoskeleton to remodel chromatin in differentiating Th cells

Abstract: Summary Following their first interaction with the antigen, quiescent naive T-helper (Th; CD4 + ) cells enlarge, differentiate, and proliferate; these processes are accompanied by substantial epigenetic alterations. We showed previously that the epigenetic regulators the polycomb-group (PcG) proteins have a dual function as both positive and negative transcriptional regulators; however, the underlying mechanisms remain poorly understood. Here, we demonstrate that during Th cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 79 publications
2
2
0
Order By: Relevance
“…Moreover, we also observed that regulation of EZH2 by NO was independent of the cell type under study which is also been supported through our data in HEK-293 cells exposed to NO. In parallel to well reported function of NO 40,41 as well as EZH2 4244 in actin cytoskeleton remodeling, we observed that NO exposure caused transient localization of EZH2 on the actin cytoskeleton most likely prior to its degradation through autophagosome-lysosomal pathway. In addition, preserving the level of H3K27me3 via inhibition of demethylases reversed NO effect on cell migration.…”
Section: Discussionsupporting
confidence: 85%
“…Moreover, we also observed that regulation of EZH2 by NO was independent of the cell type under study which is also been supported through our data in HEK-293 cells exposed to NO. In parallel to well reported function of NO 40,41 as well as EZH2 4244 in actin cytoskeleton remodeling, we observed that NO exposure caused transient localization of EZH2 on the actin cytoskeleton most likely prior to its degradation through autophagosome-lysosomal pathway. In addition, preserving the level of H3K27me3 via inhibition of demethylases reversed NO effect on cell migration.…”
Section: Discussionsupporting
confidence: 85%
“…1A, B ). Visible points of phalloidin staining are consistent with polymerized structures charted within the nucleus 15 , 30 . After CytoD, Airy magnification of the nuclear area shows polymeric actin adherent to the outer nuclear membrane forming a thick cap both above and below stained lamin A/C on cross section.…”
Section: Resultssupporting
confidence: 66%
“…Actin is also present within the nucleus 14 , and its energy-dependent import and export are regulated by extracellular processes including mechanical strain 3,4,6 . Due to the density of the nucleus, F-actin actin rarely appears as strongly phalloidin-positive strands typical of cytoplasmic F-actin, although it can be visualized as distinct actin fibers in some states such as DNA replication stress 6,15 , or transiently during mitotic exit 16 . Despite poor geographic visualization of polymerized actin, evidence suggests that a dynamic exchange between free and polymerized actin states occurs in the nucleus, and importantly, most actin polymerization modifiers, including Arps, have been found within the nucleus 14,17 .…”
mentioning
confidence: 99%
“…Inhibition of Ezh2 by small-molecule inhibitor UNC1999 diminishes the presence of nuclear F-actin, reduces the expression of β-actin, γ-actin and Vav1, leading to a more condensed organization of chromatin fibers. In summary, Ezh2 is required for the assembly of intranuclear F-actin to re-organize chromatin in differentiating Th cells ( Titelbaum et al., 2021 ).…”
Section: Main Bodymentioning
confidence: 99%